Evaluation of lymphocyte subpopulations in seropositive individuals to Helicobacter pylori - Palacios Martínez, Monika; Nájera Medina, Oralia; Gonázlez López, Marco; Ramírez Navarro, Karina; Solís Chávez, Patricia Concepción; Gutiérrez Cárdenas, Elena Marcia (Acta Universitaria, 2022)
Helicobacter pylori (H. pylori) infections are considered a public health problem due to its high morbidity rate in theMexican population. Therefore, this work is focused on the detection of anti-IgA-H. pylori by ELISA blood test andthe evaluation of lymphocyte subpopulations by flow cytometry in peripheral blood of adult population from a rural area of the state of Morelos. We worked with 79 adult participants (aged 42 ± 13.7 years), of which 57% (n = 45) wereseropositive and 43% (n = 24) seronegative. No statistically significant differences were found in leukocytes, or effectorcells, only a small tendency to increase both CD4+ and CD8+ memory cells, in H. pylori seropositive individuals, anda decrease in double positive CD8+ cells (CD8+CD45RA+CD45RO+, p < 0.05). There are probably no relevant differences due to the capacity of the bacterium to evade the immune response.